Mesoporous MnO2/SBA-15 as a synergetic adsorbent for enhanced uranium adsorption. (4th August 2020) - Ding, Yi; Xian, Qiang; Wang, Enchao; He, Xinmiao; Jiang, Zhengdi; Dan, Hui; Zhu, Wenkun
Abstract : Mesoporous MnO2 /SBA-15 composites were prepared via a simple route and were explored as a synergetic adsorbent for adsorption of U(vi ). Abstract : Mesoporous MnO2 /SBA-15 composites were prepared via a simple route using KMnO4 and MnCl2 as Mn sources for the first time and were explored as a synergetic adsorbent for the removal of U(vi ). The results demonstrated that the U(vi ) adsorption capacity of both pristine SBA-15 and MnO2 can be greatly enhanced by combining them. MnO2 /SBA-15 composites exhibited remarkable U(vi ) adsorption capacity. The 40%MnO2 /SBA-15 sample with optimum MnO2 content exhibited a maximum U(vi ) adsorption capacity of 465.1 mg g −1, which is much higher than those of pristine SBA-15, MnO2 and many other adsorbents. The U(vi ) adsorption process was well fitted by the Langmuir model and the pseudo-second order model. The thermodynamic data analyses revealed that the U(vi ) adsorption process was spontaneous and endothermic. It was proposed that the synergetic effect played an important role in the U(vi ) adsorption process. These results demonstrated that the MnO2 /SBA-15 composites can be employed as a promising U(vi ) adsorbent.